PENGARUH OBAT ANTI HIPERTENSI, PERUBAHAN GAYA HIDUP SERTA PERAN KELUARGA DALAM MANAJEMEN HIPERTENSI TERHADAP GOLD TREATMENT HIPERTENSI PADA PASIEN RUMAH SAKIT BUNDA HALIMAH BATAM - Isramilda; Andi Ipaljri Saputra; Yevi Aprillia (Universitas Batam, 2026)
Background: Hypertension is a major health concern in Indonesia and worldwide, often associated with unhealthy dietary patterns and a sedentary lifestyle. This condition increases the risk of cardiovascular diseases, which can lead to severe complications and even death. Effective hypertension management involves pharmacological therapy with antihypertensive drugs, lifestyle modifications, and family support to help patients achieve optimal treatment targets. Methods: This study mploye dan analytical observational design with a cross-sectional approach. The sample consisted of 124 hypertensive patients who met the inclusion and exclusion criteria. Data were collected using a questionnaire and analyzed using the Spearman correlation test to examine the relationship between antihypertensive drug adherence, lifestyle changes, and family support in achieving successful Gold Treatment hypertension management. Results: The findings indicated a significant relationship between adherence to antihypertensive medication, the adoption of a healthy lifestyle, and family support in achieving successful hypertension management based on the GOLD Treatment approach. These factors play a crucial role in controlling blood pressure and improving patients’ quality of life. Conclusion: Optimal hypertension management requires a comprehensive approach that includes regular medication adherence, healthy lifestyle changes, and active family involvement in supporting patients. Implementing these strategies can enhance treatment effectiveness and reduce the risk of hypertension-related complications.